Basic principles of sensorimotor adaptation to different distortions with different effectors and movement types: a review and synthesis of behavioral findings - Bock, Otmar (Frontiers in Human Neuroscience, 2013)
This article reviews seemingly conflicting behavioral data about sensorimotor adaptation. Some earlier studies assert that one common mechanism exists for multiple distortions, and others that multiple mechanisms exist for one given distortion. Some but not others report that adaptation is direction-selective. Some submit that adaptation transfers across effectors, and others that a single effector can adapt to multiple distortions. A model is proposed to account for all these findings. It stipulates that adaptive mechanisms respond to multiple distortions, consist of directionally tuned special-purpose modules, can be switched in dependence on contextual cues, and are connected to practiced movement types with a higher weight than to unpracticed ones.